2021
DOI: 10.3390/s21206915
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Sensor for the Monitoring of Arterial Pulse Wave: Detection of Arrhythmia Occurring in PAC/PVC Patients

Abstract: Previous studies have found that the non-invasive blood pressure measurement method based on the oscillometric method is inaccurate when an arrhythmia occurs. Therefore, we propose a high-sensitivity pulse sensor that can measure the hemodynamic characteristics of the pulse wave and then estimate the blood pressure. When an arrhythmia occurs, the hemodynamics of the pulse wave are abnormal and change the morphology of the pulse wave. Our proposed sensor can measure the occurrence of ectopic beats from the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A critical prerequisite to determine valid PTT is to detect and deliver a reliable PW morphology. Previous studies with piezo-based sensors have been able to detect reliable PW's amongst healthy volunteers [18,19], volunteers with arrythmias [20],and hypertensive volunteers [13]. In a clinical setting, Clemente et al, also demonstrated a reliable beat-to-beat PW detection rate in a small cohort of ICU patients [21].…”
Section: Prior Pes/pec Researchmentioning
confidence: 97%
“…A critical prerequisite to determine valid PTT is to detect and deliver a reliable PW morphology. Previous studies with piezo-based sensors have been able to detect reliable PW's amongst healthy volunteers [18,19], volunteers with arrythmias [20],and hypertensive volunteers [13]. In a clinical setting, Clemente et al, also demonstrated a reliable beat-to-beat PW detection rate in a small cohort of ICU patients [21].…”
Section: Prior Pes/pec Researchmentioning
confidence: 97%
“…In this research, the window size of the dynamic threshold calculation is set to be the same as the sampling rate, which can have an excellent dynamic adaptation to detect regular or irregular pulse waves. In our previous study [45], the window size could be set to half the sampling rate for patients with arrhythmia. The gain can adjust the dynamic threshold level, and we set it 1.1 times in this study.…”
Section: Pulse Wave Signal Processingmentioning
confidence: 99%
“…In previous studies, we developed a piezoelectric sensor and algorithm [16] that can be used for PWV detection. Fig.…”
Section: A Local Pwv Measurementmentioning
confidence: 99%